2021
DOI: 10.1086/713787
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Crime

Abstract: We thank SafeGraph, Inc. for making their data available for research. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research.NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 96 publications
(44 citation statements)
references
References 17 publications
0
44
0
Order By: Relevance
“…What is less understood is why families living in metropolitan counties and counties with more black residents might be at increased risk for supervisory neglect as compared to other counties. Other studies have found that domestic violence (including child abuse) was more likely to be reported in neighborhoods with more renters than homeowners, which may indicate the different experiences for those in especially tight quarters (Bullinger et al, 2021). For counties with more black residents, parents/caretakers may have been more likely to be frontline workers (Blau et al, 2021) leading to greater difficulty in finding appropriate, affordable, and available childcare when schools and daycares closed.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…What is less understood is why families living in metropolitan counties and counties with more black residents might be at increased risk for supervisory neglect as compared to other counties. Other studies have found that domestic violence (including child abuse) was more likely to be reported in neighborhoods with more renters than homeowners, which may indicate the different experiences for those in especially tight quarters (Bullinger et al, 2021). For counties with more black residents, parents/caretakers may have been more likely to be frontline workers (Blau et al, 2021) leading to greater difficulty in finding appropriate, affordable, and available childcare when schools and daycares closed.…”
Section: Discussionmentioning
confidence: 97%
“…COVID-19 has increased risk factors associated with child maltreatment perpetration, such as unemployment, reduced income, alcohol abuse, intimate partner violence, and limited social support (Catalá-Miñana et al, 2017;Lindo, Schaller, & Hansen, 2018;Lowell & Renk, 2017;Schenck-Fontaine, Gassman-Pines, Gibson-Davis, & Ananat, 2017). Research from Florida (Baron et al, 2020), Indiana (Bullinger et al, 2020b), and Chicago, Illinois (Bullinger et al, 2021), suggests that child maltreatment allegations, substantiated cases of child maltreatment, and calls to 911 reporting child abuse, respectively, were lower than expected. In contrast, other data sources such as social media accounts and poison control records suggest that children were exposed to more violence and less supervision (Babvey et al, 2020;Chang et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…A notable exception is Japan, where suicide statistics are reported frequently and have already been subject to scientific analysis within the COVID-19 context [20]. Higher-frequency monitoring has been performed in the context of the COVID-19 pandemic based on online searches as recorded by Google Trends [13,[21][22][23], by tracking visits to emergency departments [24,25], and by monitoring calls to the police for help with domestic disputes [26][27][28]. In line with our findings, the available evidence based on such indicators suggests that the COVID-19 pandemic has had significant deleterious effects on public mental health [29,30].…”
mentioning
confidence: 99%